117 Social Determinants of Health and Spine Tumor Surgery Outcomes: A Nationwide Analysis of Disparities from 2002-2019. (April 2023) - Tang, Oliver Young; Ayala, Cameron; Feler, Joshua; Rivera Perla, Krissia M.; Bajaj, Ankush; Ganga, Arjun; Fridley, Jared; Toms, Steven A.; Gokaslan, Ziya L.; Sullivan, Patricia Zadnik
Abstract : INTRODUCTION: Earlier research has demonstrated that social determinants of health (SDoH) impact neurosurgical access and outcomes, influencing patient disparities. METHODS: We identified all admissions with a spine tumor diagnosis in the National Inpatient Sample from 2002-2019. Four SDoH were analyzed: race and ethnicity, insurance, household income, and safety-net hospital (SNH) treatment. Hospitals in the top quartile of safety-net burden (percentage of patients receiving Medicaid or uninsured) were categorized as SNHs. Multivariable regression queried the association between 22 variables and six perioperative outcomes: mortality, discharge disposition, complications, length of stay (LOS), and hospitalization costs. Relative importance of predictors for disposition were assessed using random forest models. RESULTS: Of 6, 593, 391 total admissions with spine tumors, 219, 380 (3.3%) underwent surgery. Non-white race (odds ratio [OR] = 0.80–0.91, P = 0.001) and non-private insurance (OR = 0.76–0.83, p = 0.001) were associated with lower odds of surgery. Among surgical admissions, presenting severity, including myelopathy and plegia, was elevated among nonwhite, non-private insurance, and low-income admissions (all P = 0.001). Black race (OR = 0.70, P = 0.001), Medicare (OR = 0.70, P = 0.001), Medicaid (OR = 0.90, P = 0.001), and lower income (OR = 0.88–0.93, all P = 0.001) were associated with decreased odds of favorable discharge disposition. Elevated LOS and costs were observed among non-white (LOS: +6-10%, costs: +5-9%, both P = 0.001) and Medicaid (LOS: +16%, costs: +6%, both P = 0.001) admissions. SNH treatment was also associated with higher mortality (OR = 1.49, P = 0.001) and complications (OR = 1.20, P = 0.001). From 2002-2019, disposition improved annually for Medicaid patients (OR = 1.03 per year, P = 0.022) but worsened for Black patients (OR = 0.98 per year, P = 0.046). Random forest models identified household income as the most important disposition predictor. CONCLUSIONS: For spine tumor admissions, SDoH predicted surgical intervention, presenting severity, and perioperative outcomes. Over two decades, disparities improved for Medicaid patients but worsened for Black patients.